Aspects of pre-eclamptic toxaemia of pregnancy, consanguinity, twinning in Ankara. Issue 1 (February 1976) - Stevenson, A C; Say, B; Ustaoglu, S; Durmus, Z
Abstract : It appears that women classed as having pre-eclamptic toxaemia are less frequently consanguineous with their husbands than all other mothers and in particular those mothers classed as having pregnancies complicated by chronic hypertensive disease. Search revealed no evidence for possible biases which could have stimulated such findings. Further evidence is advanced suggesting that, though pre-eclamptic toxaemia is more common in all types of twin pregnancies than in single births, it is more common where the twins are dizygous than where they are monozygous. It is pointed out that both these findings would be expected if there was a contribution to the aetiology of pre-eclamptic toxaemia by maternal/fetal immunological incompatibility. However, if such a mechanism exists it is not always determined at the same gene locus.